Pengaruh Komik Asing terhadap Visualisasi Perkembangan Komik di Indonesia - Hasian, Irene; Mardika, Andri Sakti (Magenta | Official Journal STMK Trisakti, 2017)
Development of Indonesian comics that has been more than 80 years old is very rarely being topic of scientific study, especially about the history and its realitionship with foreign comics. Comics Industry in Indonesia is dominated by foreign comics, especially manga. Because of the popularity of manga comics in Indonesia, many Indonesian comics have similar visual appearance with the manga. The effect of foreign comics which is familiar by the author. This influence creates an ambiguity of identification Indonesian original comics. This reinforces the author desire to examine the historical development of comics in Indonesia and how far the influence of foreign comic visualization. The method used in this research is a qualitative approach. The explanation of the research methods for the required data will be divided into several different sub chapters. Phases of the research starting from data collection, sampling process, analyzing process, to conclusion. The author uses a random sample representing each decade which are similar with foreign comics. The analysis focused on a visual comic sample that includes panel, the viewing angle and the size of the image in the panel, ditch, bubling, and illustration. Conclusions are taken based on visual analysis of the entire Indonesian comics and foreign comics, and also from the results of both.